Comparison of Eloquent ORM with Query Builder in Work Management System (Case Study: Muhammadiyah Lamongan Hospital) - Akhdani, Febryan; Wijayanto, Danur (SENATIK STT Adisutjipto, 2022)
A management system is a set of policies, processes, and procedures used by an organization to ensure that the system can fulfill the tasks required to achieve its objectives. With this system, the company can make it easier for the management of a task/project that is being done by the employee/employee. In the SIRS Unit at Lamongan Muhammadiyah Hospital, the implementation of Work Management is still done manually, namely by holding monthly meetings held at the beginning of the month which can affect the efficiency and effectiveness of employees in terms of collecting/reporting tasks assigned by the project leader. For this reason, a Job Management System is needed that can overcome these problems. Job Management System, created on a Web-based basis using Laravel 8.0 as the framework and MySQL as the database. In this study, researchers will focus on implementing Eloquent ORM which is a special feature in Laravel to make it easier for developers to process data and compare Eloquent ORM with Query builder in its implementation on Job Management System. The result of this research is Query Builder can execute database query more faster and more memory efficient than Eloquent, but Eloquent use simple code than Eloquent.